Opiods - Koob, George F. (Neurobiology of addiction, 2023)
A current survey and synthesis of the most important findings in our understanding of the neurobiological mechanisms of addiction is detailed in our Neurobiology of Addiction series, each volume addressing a specific area of addiction. Opioids, Volume 4 in the series, explores the molecular, cellular and systems in the brain responsible for opioid addiction using the heuristic three-stage cycle framework of binge/intoxication, withdrawal/negative affect, and preoccupation/anticipation.